Kualitas Layanan Surat Keterangan Tidak Mampu di Kantor Kelurahan Talise Kecamatan Mantikulore Kota Palu - Ade Irma (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the service quality of the Certificate of Poor at the Talise Village Office, Mantkulore District, Palu City. This type of research is a qualitative research method, and the type of research used is descriptive. The data collection technique used is observation. The number of informants is 5 (five) people, namely the Village Head, Head of Community Empowerment and Social Welfare and 3 (three) residents. Interview and document review. This study uses 4 (four) aspects to measure service quality, namely speed of service, accuracy of service, ease of service and fairness of service. From the results of the study, it can be seen that the Certificate of Unable to Service at the Talise Village Office, Mantikulore District, Palu City still gets a fairly good response from informants and this result must be maintained so that the quality of service is better and optimal.